Immune Cell Dynamics Unfolded by Single-Cell Technologies - Kunz, Daniel J.; Gomes, Tomás; James, Kylie R. (Frontiers in Immunology, 2018)
The single-cell revolution is paving the way towards the molecular characterisation of every cell type in the human body, revealing relationships between cell types and states at high resolution. Changes in cellular phenotypes are particularly prevalent in the immune system, and can be observed in its continuous remodelling up to adulthood, response to disease and development of immunological memory. In this review, we delve into the world of cellular dynamics of the immune system. We discuss current single-cell experimental and computational approaches in this area and the discoveries they have led to, including insights into fate commitment and plasticity between cell fates. Finally, we provide an outlook on upcoming technological developments and predict how these will improve our understanding of the immune system.